Pengaruh Kurs Dollar Amerika Serikat, Harga Impor, Harga Domestik, Jumlah Produksi Terhadap Volume Impor Daging Sapi Di Indonesia Tahun 1998- 2013 - Pinandra Putra, Anak Agung Bagus Surya Okto; Rustariyuni, Surya Dewi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Commodity beef is a commodity with enthusiasts the highest compared to other meat commodities such as meat goat, buffalo and pigs. High protein content in beef is the consumer's choice to increase the consumption of beef. This study aims to determine the exchange rate of the US dollar, the price of imports, domestic prices and production quantities of the volume of imports of beef in Indonesia in 1998 - 2013 by using multiple linear regression analysis tenknik. The results showed that the US dollar exchange rate, the price of imports, domestic prices and production quantities simultaneous effect on the volume of imports of beef in Indonesia in 1998 - 2013 while partially obtained that the US dollar exchange rate, the price of imports, domestic prices have no significant effect the volume of imports of beef in Indonesia in 1998 - 2013 and the number of production significantly influence the volume of imports of beef in Indonesia 1998 - 2013.Berkaitan with the results of the research, the authors suggest increasing the quantity of national beef production so as to meet domestic consumption and ultimately reduce the amount of imports and resulting in the production of beef is equivalent to beef imports, so that it can satisfy people's consumption. Improving the quality of beef production in a manner free from foot and month disease infectious diseases (FMD) so that consumers do not hesitate to choose beef imports.
Keywords: Commodity beef is a commodity with enthusiasts the highest compared to other meat commodities such as meat goat, buffalo and pigs. High protein content in beef is the consumer' s choice to increase the consumption of beef. This study aims to determine the